Comparison of Treatment Response before and after Antiobsessivae Therapy among Psychiatric Patients with Obsessive Compulsive Disorder - Belbase, Mohan; Adhikari, Jyoti (Journal of Nepalgunj Medical College, 2022)
Introduction: Obsessive compulsive disorder is a common, chronic and disabling disorder marked by obsessions and/or compulsions. This study tries to find the demographic profiles, severity and response of antiobsessive drugs in young and adult patients with obsessive compulsive disorder.Aims: To study the socio-demographic profile, severity and treatment response to commonly used antiobsessive medications in male and female, and young and adults.Methods: This is a hospital based experimental study done in patients attending to psychiatry out-patient department over one year from February 2020 to January 2021.  Diagnosis of obsessive compulsive disorder was made based on International Classification of Disease- 10 criteria for research. Yale-Brown obsessive compulsive scale check list (adult and children) was applied in those patients and recorded accordingly on baseline (week 0) and patients were treated with specific serotonin reuptake inhibitors or tricyclic antidepressants in therapeutic doses for 6 weeks. On follow up at week 6, they were again reassessed and the scores were recorded and analyzed.Results: Among the total study subject (N-52), 26(50 %) were male and 26(50 %) were females. Patients in age bracket 20-29 is the most common age group representing 18(34.6 %). Mean age of patients is 30.36±11.93 years (28.65±9.80 in male and 32.04±13.73 in female). Severe form of obsessive compulsive disorder was the most common type that represent 33(63.5%) followed by moderate 16(30.8%) and extreme 3(5.7%). There is a difference of treatment response of antiobsessive therapy in male and female with statistical significance (p= 0.039).Conclusion: This study shows that obsessive compulsive disorder is most commonly found in 20-29 age group and the severe type is the most common. There is a significant difference in treatment response of antiobsessive therapy in male and female.